2015
DOI: 10.3892/or.2015.3860
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine inhibits the proliferation of acute lymphocytic leukemia cell lines via decrease in GSK-3β

Abstract: Tetramethylpyrazine (TMP) has been proven to be an anticancer agent in many studies. However, its effectiveness in acute lymphoblastic leukemia (ALL) and its molecular mechanisms are still unclear. The present study aimed to evaluate the effect of TMP against Jurkat and SUP-B15 ALL cell lines and to investigate the possible detailed mechanism of action of TMP. A Cell Counting Kit-8 (CCK-8) assay was employed to examine the proliferation of Jurkat and SUP-B15 cells. Flow cytometric analysis was conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…However, the effect of TMP was different in various types of tumors. Previous studies have demonstrated that 200 µM TMP significantly inhibited hepatocellular carcinoma cell proliferation (25) and that 300 µg/ml TMP significantly inhibited the viability of acute lymphocytic leukemia cell lines (26). These results were similar to the results of the present study where it was observed that breast cancer cells were inhibited by 1,600 µM TMP.…”
Section: Discussionsupporting
confidence: 92%
“…However, the effect of TMP was different in various types of tumors. Previous studies have demonstrated that 200 µM TMP significantly inhibited hepatocellular carcinoma cell proliferation (25) and that 300 µg/ml TMP significantly inhibited the viability of acute lymphocytic leukemia cell lines (26). These results were similar to the results of the present study where it was observed that breast cancer cells were inhibited by 1,600 µM TMP.…”
Section: Discussionsupporting
confidence: 92%
“…In pediatric ALL cells, the GSK-3β/NFKB relationship has already been studied [20][21][22][23]; however, while the results suggest an influence of GSK-3β on the transcriptional activity of NFKB p65, there were no changes in its expression in this initial approach. On the other hand, the use of selective GSK-3β inhibitors is a target in the treatment of pediatric ALL.…”
Section: Discussionmentioning
confidence: 91%
“…The molecular signaling pathways associated with the hematopoiesis process are varied but deregulation in one or more points should be decisive in ALL development. Moreover, the cytogenetic pattern is an important determinant of ALL development; for example, t (1,19), t (4,11), t (12,21) and t (9,22) affect the expression of the enzymes that regulate the intracellular signaling process [1]. As we know, immunophenotype, age, race, white blood cell (WBC) count, and gender are important prognostic factors.…”
mentioning
confidence: 99%
“…The most common inhibitors are small synthetic molecules that compete for ATP binding site [15][16][17]. Recently, Wang has reported that tetramethylpyrazine inhibits the proliferation of ALL cell lines decreasing in GSK-3β signaling, an interesting pharmacological perspective to development [20]. Layton et.al, report that NFKB relative expression levels, in comparison to the GSK-3β immunohistochemistry results of the bone marrow samples, showed a significant difference between positive and negative cases, these results suggest that GSK-3β may be a prognostic biomarker in childhood ALL [21].…”
Section: Perspectivesmentioning
confidence: 99%